2012
DOI: 10.1029/2011tc003021
|View full text |Cite
|
Sign up to set email alerts
|

Surface expression of eastern Mediterranean slab dynamics: Neogene topographic and structural evolution of the southwest margin of the Central Anatolian Plateau, Turkey

Abstract: The southwest margin of the Central Anatolian Plateau has experienced multiple phases of topographic growth, including the formation of localized highs prior to the Late\ud Miocene that were later affected by wholesale uplift of the plateau margin. Our new biostratigraphic data limit the age of uplifted marine sediments at the southwest plateau margin at 1.5 km elevation to <7.17 Ma, and regional lithostratigraphic correlations\ud imply that the age is <6.7 Ma. Single-grain CA-TIMS U-Pb zircon analyses from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
130
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 90 publications
(133 citation statements)
references
References 147 publications
(210 reference statements)
2
130
1
Order By: Relevance
“…We have no evidence that N-S shortening has affected our study area yet and conclude that the causes of this compression should be restricted to an area east of the Western Taurides, for instance, induced by collision of Cyprus with Turkey reflected in late Miocene shortening of the Kyrenia range (e.g. Schildgen et al 2012a;McCay and Robertson 2013).…”
Section: Regional Implicationsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have no evidence that N-S shortening has affected our study area yet and conclude that the causes of this compression should be restricted to an area east of the Western Taurides, for instance, induced by collision of Cyprus with Turkey reflected in late Miocene shortening of the Kyrenia range (e.g. Schildgen et al 2012a;McCay and Robertson 2013).…”
Section: Regional Implicationsmentioning
confidence: 99%
“…Seismic tomographic images of van Hinsbergen et al (2010c) and Biryol et al (2011) clearly show that the Antalya slab is disconnected from the Aegean slab along a prominent transform (STEP, Govers and Wortel 2005). Biryol et al (2011) and Schildgen et al (2012a) suggested that the Antalya slab is a fragment of the Cyprus slab that for some reason rotated into a N-S orientation. Instead, we suggest that the thrust that the Antalya slab formed as a result of a separate, N-S striking subduction zone, that dips eastwards and until at least Pliocene time connected to the surface along the Aksu thrust and its offshore equivalents, with Bey Dağları in the lower plate, and the Taurides in the upper plate.…”
Section: Regional Implicationsmentioning
confidence: 99%
See 3 more Smart Citations